Demam berdarah dengue di Kota Bima Nusa Tenggara Barat Indonesia - Solikhah; Suwarno; Puput Septian Permatasari (MEDIA ILMU KESEHATAN, 2021)
Background: Dengue hemorrahagic fever (DHF) remains public health problem in some areas in Indonesia. As a tropical country, supported by heavy rainfall subsequently caused extraordinary events dengue every year. The low level of knowledge, attitudes and behavior of the Indonesian regarding how to prevent and manage dengue has become a trigger for outbreaks in several parts of Indonesia. Objective: This study aimed to describe the incidence of dengue fever in the Bima city, East Nusa Tenggara Indonesia in 2020. Methods: This study used mix-method approach. Quantitative data were obtained from secondary data on dengue cases from January to July 2020 and in-depth interviews with the managers of the disease surveillance program at the Bima City Health Office. Results: The results of this study showed that the increase in the number of dengue cases from 2019 was 144 cases. While in 2020 the increase in dengue cases occurred in the Jatibaru Puskesmas work area in March 2020 as many as 246 cases. The majority of DHF sufferers are female and aged 5-9 years. Conclusion: Cross-program cooperation in health promotion efforts in the City of Bima needs to be increased to motivate the community to always carry out Clean and Healthy Living Behaviors (as well-known PHBS).